Multimodal Responses of Self‐Organized Circuitry in Electronically Phase Separated Materials. (13th July 2016) - Herklotz, Andreas; Guo, Hangwen; Wong, Anthony T.; Lee, Ho Nyung; Rack, Philip D.; Ward, Thomas Z.
Abstract : Confining an electronically phase separated manganite film to the scale of its coexisting self‐organized metallic and insulating domains allows resistor‐capacitor circuit‐like responses while providing both electroresistive and magnetoresistive switching functionality.